Mesenchymal Stem Cells as Vectors for Lung Disease - Loebinger, Michael R. (American Thoracic Society, 2008)
Stem cells divide asymmetrically, leading to self-renewal and the production of a daughter cell committed to differentiation. This property has engendered excitement as to the use of these cells for treatments. The majority of the work with stem cells has used the relatively accessible and well-characterized adult bone marrow stem cell compartment. Initially the focus of this research was on the potential for these stem cells to repair damaged organs by differentiating into epithelial cells to replace the injured areas. More recently it has become clear that engraftment of these stem cells as epithelial tissue is a rare event with perhaps limited clinical significance. Despite this, stem cells appear to have the ability to home to and be specifically recruited to areas of inflammation and injured tissues often characterized by excessive extracellular matrix deposition. As a consequence they are intimately involved in regions of physiological and pathological repair. Coupled with this, autologous hematopoietic stem cells, or the relatively immunoprivileged mesenchymal stem cells, can be expanded and engineered ex vivo and reintroduced without immunomodulation. The prospect of using such cells clinically as a cellular therapy holds much promise for many conditions and organ pathologies. Here we address the evidence for the incorporation of bone marrow stem cells into areas of stroma formation as a prelude to possible future treatment options for common lung diseases.